2014
DOI: 10.7567/jjap.53.04ec11
|View full text |Cite
|
Sign up to set email alerts
|

Influence of work function variation of metal gates on fluctuation of sub-threshold drain current for fin field-effect transistors with undoped channels

Abstract: Influence of work function variation (WFV) in metal gates (MGs) on fluctuation of sub-threshold drain current is investigated in detail by analyzing fluctuation of current–onset voltage (COV) for fin field-effect transistors (FinFETs) with polycrystalline TiN and amorphous TaSiN MGs. The polycrystalline TiN MG exhibits anomalously increased COV fluctuation of the nMOS FinFETs in comparison to the pMOS case, while the amorphous MG exhibits well suppressed COV fluctuation both for the n- and pMOS FinFETs. Throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…). These lateral variations of the EWF will directly be reflected in lateral variations of V bi , leading to variability of threshold voltages and degrading the sub‐threshold slope of transistor transfer characteristics . Again, the question arises concerning the applicability of the vacuum WF variability values, known from surface microscopy studies, to the electrostatics of the interfaces.…”
Section: Introductionmentioning
confidence: 99%
“…). These lateral variations of the EWF will directly be reflected in lateral variations of V bi , leading to variability of threshold voltages and degrading the sub‐threshold slope of transistor transfer characteristics . Again, the question arises concerning the applicability of the vacuum WF variability values, known from surface microscopy studies, to the electrostatics of the interfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Values of uncertain orientation-dependent work functions (WKs) of gate material causes WK fluctuation (WKF). Many studies have surveyed WKF for different devices [3,10,11,12,13,14,15,16], and some have further discussed the distribution of metal grains on planar metal–oxide–semiconductor field-effect transistors (MOSFETs) [17,18]. However, seldom do these studies put emphasis on gate-all-around (GAA) nanowire (NW) MOSFET devices.…”
Section: Introductionmentioning
confidence: 99%
“…WKF-induced circuit variations, such as timing and power fluctuations [26,27,28], seriously affect the dynamic property of GAA NW CMOS circuits. Most previous research only focused on the DC characteristics of N-type planar or fin-typed MOSFET devices when considering the aforementioned variability [10,28,29,30]. Various fluctuations of circuit characteristics, such as noise margin (NM), timing, and power consumption are also important to research, but the variability of GAA NW CMOS circuits has not been clearly studied yet.…”
Section: Introductionmentioning
confidence: 99%
“…It was demonstrated that the threshold-voltage variability of advanced FET devices caused in part by work function variation in granular TiN gate electrodes. [1] As TiN films consist of small grains with a size of 3-20 nm and different crystal orientations, [2] random distribution of the nano-crystals causes work function (WF) variation along the film. Therefore, measurements of the WF variation for individual TiN grains with high spatial resolution are an important challenge.…”
Section: Introductionmentioning
confidence: 99%